2003
DOI: 10.1530/eje.0.1490449
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of galectin-3 in diseases of the thyroid gland

Abstract: Objective: Malignant tumors of the thyroid gland exhibit a variety of histopathologies and clinical behavior. Immune markers are gaining more and more importance in diagnostic pathology, especially in the differential diagnostics and in the grading of thyroid gland tumors. Design: The authors investigated the immunohistochemical reaction of galectin-3 (gal3) in patients with various thyroid gland diseases. They tested the diagnostic value of gal3 in determining the benign or malignant nature of various lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 27 publications
6
39
1
1
Order By: Relevance
“…The absence of galectin-3 detection in thyroid carcinomas and the presence of galectin-3 in benign thyroid lesions have been previously reported by others (Kovacs et al, 2003), even in the large study by Bartolazzi, which demonstrated high sensitivity and specificity (490%) of galectin-3 as a marker of malignant thyroid lesions (Bartolazzi et al, 2001). In the present study, a relatively high number of benign lesions were positive for galectin-3, namely in the subgroup of undeterminate lesions, two out of 22 benign lesions (9%).…”
Section: Discussionsupporting
confidence: 71%
“…The absence of galectin-3 detection in thyroid carcinomas and the presence of galectin-3 in benign thyroid lesions have been previously reported by others (Kovacs et al, 2003), even in the large study by Bartolazzi, which demonstrated high sensitivity and specificity (490%) of galectin-3 as a marker of malignant thyroid lesions (Bartolazzi et al, 2001). In the present study, a relatively high number of benign lesions were positive for galectin-3, namely in the subgroup of undeterminate lesions, two out of 22 benign lesions (9%).…”
Section: Discussionsupporting
confidence: 71%
“…Other investigators have used Gal-3 in differentiating FTC from FA in fine needle aspirates (16); however, Gal-3 expression has also been reported in benign thyroid lesions (41,42). We found a reasonable accuracy (88%) in the differential diagnosis between FA and FVPTC for Gal-3.…”
Section: Discussionsupporting
confidence: 61%
“…The follicular cells entrapped in areas of great chronic lymphocyte inflammation were also positive. This is in agreement with Kova´cs et al (14) and Herrmann et al (9). Rabinovich and Rubinstein (15) stated that the most likely explanation for the Gal3 expression of non-neoplastic follicular cells in an inflamed area is neosynthesis affected by cytokines secreted by inflammatory cells or the simple permeation of Gal3 abundantly shed by lymphocytes into the neighboring follicular cells.…”
Section: Discussionsupporting
confidence: 93%